2012
DOI: 10.1002/hrm.21498
|View full text |Cite
|
Sign up to set email alerts
|

Servant leadership, organizational identification, and work‐to‐family enrichment: The moderating role of work climate for sharing family concerns

Abstract: The present study investigates the impact of servant leadership as perceived by followers on their work‐to‐family enrichment (WFE) by focusing on the mediating role of organizational identification and the moderating role of work climate for sharing family concerns. The results from a field survey of 230 married managers in China provide full support for our hypotheses, indicating that perceived servant leadership is positively related to WFE; this relationship is also mediated by organizational identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
162
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(168 citation statements)
references
References 42 publications
4
162
0
2
Order By: Relevance
“…A second study reported that a serving culture mediated the relationship between servant leadership and employee identification [23]. A third related study indicated that servant leadership enhances organisational identification [85].…”
Section: Team Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…A second study reported that a serving culture mediated the relationship between servant leadership and employee identification [23]. A third related study indicated that servant leadership enhances organisational identification [85].…”
Section: Team Outcomesmentioning
confidence: 99%
“…Another study showed that organisational identification mediated the relationship between servant leadership and work-to-family enrichment [85].…”
Section: Individual Outcomesmentioning
confidence: 99%
“…Viewing company as a "big family," Chinese employees prefer to receive those benefits which directly support their family issues (Zhang, Kwong Kwan, Everett and Jian, 2012). Moreover, Chinese employees expect to obtain support from their supervisors, organizations and family (Spector et al, 2007).…”
Section: Chinese Family Orientationmentioning
confidence: 99%
“…By organizations in China offering an equal distribution of direct family benefits to employees, managers may also reduce the perceived high power distance among employees and employers. In terms of the work-family benefits from organizations, Chinese employees prefer to receive the benefits which are meant for their family members, such as medical care for children, elder and sponsors (Zhang, Kwong Kwan, Everett and Jian, 2012). The study of I-deals under Chinese context proved that Chinese employees prefer to negotiate demand beyond work boundaries to perceive more enrichment (Tang and Hornung, 2015).…”
Section: Collectivismmentioning
confidence: 99%
“…Servant leaders imbue the meaning of and reinforce the importance of serving others within and outside the organization through their behavior, which provides crucial cues that serving others is a distinctive characteristic of the organization (Zhang et al, 2012). According to Spears (2004) Greenleaf (1970) wrote and said that this simple fact is the key to leader greatness.…”
Section: Service Orientationmentioning
confidence: 99%